2016
DOI: 10.1039/c5ob02107c
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and in vitro evaluation ofd-glucose-based cationic glycolipids for gene delivery

Abstract: Glycolipids might become a new type of promising non-viral gene delivery systems because of their low cytotoxicity, structural diversity, controllable aqua-and lipo-solubility, appropriate density and distribution of positive charges, high transfer efficiency and potential targeting function. In this study, four kinds of L-arabinose-based cationic glycolipids (Ara-DiC12MA, Ara-DiC14MA, Ara-DiC16MA and Ara-DiC18MA) containing quaternary ammonium as hydrophilic headgroup and two alkane chains as hydrophobic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…For Malt-DiC16MA liposome, the density of GFP cells increased with increase of N/P ratio but the fluorescent protein expression was weaker integrally than Malt-DiC14MA lipoplexes. However, the transfection efficiency of glucose-based lipids with the hydrophobic tails (C14 or C16) on the positively charged nitrogen atoms were as good as or better than lipo2000 [ 37 ]. Simultaneously, the lack of transfections of Malt-DiC12MA liposomes under different N/P ratios and the other two liposomes (Malt-DiC14MA and Malt-DiC16MA) at N/P of 2:1 were also observed, which corresponded with the glucose-based cationic liposomes with hydrophobic tails (C12) at all the N/P ratios and (C14 and C16) at low N/P ratios.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Malt-DiC16MA liposome, the density of GFP cells increased with increase of N/P ratio but the fluorescent protein expression was weaker integrally than Malt-DiC14MA lipoplexes. However, the transfection efficiency of glucose-based lipids with the hydrophobic tails (C14 or C16) on the positively charged nitrogen atoms were as good as or better than lipo2000 [ 37 ]. Simultaneously, the lack of transfections of Malt-DiC12MA liposomes under different N/P ratios and the other two liposomes (Malt-DiC14MA and Malt-DiC16MA) at N/P of 2:1 were also observed, which corresponded with the glucose-based cationic liposomes with hydrophobic tails (C12) at all the N/P ratios and (C14 and C16) at low N/P ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Among these cationic lipids, carbohydrates-based cationic lipids have been drawn great attention [ 28 , 29 , 30 , 31 ] because carbohydrates and their derivatives (such as, glycans, proteoglycans, glycoproteins, or glycolipids [ 32 , 33 ]) played key roles in a wide range of biological processes including cell-cell informational reception and transmission, cell growth and metastasis, cell adhesion intercellular identification and immunity [ 34 , 35 , 36 ]. Furthermore, lots of studies have shown that glycoside ligand could be acted as a targetable ligand for receptors, such as galactose, mannose, glucose and hyaluronic acid [ 30 , 31 , 37 , 38 , 39 ], which overexpressed in the surface of cancer cells. Therefore, carbohydrates may be conjugated in targeted gene delivery system with high transfer efficiency and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guided by the structure-function relationship, lots of biodegradable and commercial available chemicals such as amino acids [41], oligopeptide [42], cholesterol [43, 44], cyclen [45] and carbohydrates [46, 47] were commonly selected as the backbone of cationic lipids to improve the transfection efficiency and targeting delivery. In recently, more and more carbohydrates-based cationic lipids [48], were designed and synthesized for the reason that carbohydrates are involved in many important physiological processes, including inflammatory and immunological responses, tumor metastasis, cell-cell signaling, apoptosis, cell adhesion, bacterial and viral recognition, and anticoagulation [49]. In addition, carbohydrates are specific ligands to targeting cell surface receptors, which receive significant attention in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor-mediated endocytosis is promoted to cellular uptake capacity in gene delivery [50]. The ligands corresponding to cell surface receptors including glucose [48, 51], galactose [50, 52], mannose[53], hyaluronic acid (HA) [54] and so on, which have been conjugated in gene delivery vectors.…”
Section: Introductionmentioning
confidence: 99%